The Chinese Laundries of Wichita, Kansas: A Portrait of an Immigrant Community on the Western Frontier, 1880-1905 - Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2013)
The author uses historic newspaper reports, census records, city directories, and historic advertising to recreate the Chinese community found in Wichita, Kansas around the turn of the century.
Angela Schnee, “The Chinese Laundries of Wichita, Kansas: A Portrait of an Immigrant Community on the Western Frontier, 1880-1905,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/225.
Keywords: Burlingame Treaty; Mr. Lillie; Chinese Exclusion Act; Charles Sing; Kansas Pacific Railroad; Chinese Laundries